Case Report: A novel IRF2BP2 mutation in an IEI patient with recurrent infections and autoimmune disorders - Pan, Yiwen; Shang, Guoguo; Li, Jing; Zhang, Yuwen; Liu, Jianying; Ji, Yuan; Ding, Jing; Wang, Xin (Frontiers in Immunology, 2023)
Introduction: Inborn errors of immunity (IEI) are a heterogeneous group of disorders characterized by increased risk of infections, autoimmunity, autoinflammatory diseases, malignancy and allergy. Next-generation sequencing has revolutionized the identification of genetic background of these patients and assists in diagnosis and treatment. In this study, we identified a probable unique monogenic cause of IEI, and evaluated the immunological methods and pathogenic detections. Methods: A family with a member with a clinical diagnosis of IEI was screened by whole genomic sequencing (WGS). Demographic data, clinical manifestations, medical history, physical examination, laboratory findings and imaging features of the patient were extracted from medical records. Comprehensive immune monitoring methods include a complete blood count with differential, serum levels of cytokines and autoantibodies, T-cell and B-cell subsets analysis and measurement of serum immunoglobulins. In addition, metagenomic sequencing (mNGS) of blood, cerebrospinal fluid and biopsy from small intestine were used to detect potential pathogens. Results: The patient manifested with recurrent infections and autoimmune disorders, who was eventually diagnosed with IEI. Repetitive mNGS tests of blood, cerebrospinal fluid and biopsy from small intestine didn’t detect pathogenic microorganism. Immunological tests showed a slightly decreased level of IgG than normal, elevated levels of tumor necrosis factor and interleukin-6. Lymphocyte flow cytometry showed elevated total B cells and natural killer cells, decreased total T cells and B-cell plasmablasts. WGS of the patient identified a novel heterozygous mutation in IRF2BP2 (c.439_450dup p. Thr147_Pro150dup), which was also confirmed in his father. The mutation was classified as variant of uncertain significance (VUS) according to the American College of Medical Genetics and Genomics guidelines. Conclusion: We identified a novel IRF2BP2 mutation in a family with a member diagnosed with IEI. Immune monitoring and WGS as auxiliary tests are helpful in identifying genetic defects and assisting diagnosis in patients with clinically highly suspected immune abnormalities and deficiencies in inflammation regulation. In addition, mNGS techniques allow a more comprehensive assessment of the pathogenic characteristics of these patients. This report further validates the association of IRF2BP2 deficiency and IEI, and expands IEI phenotypes.